In situ reduction of graphene oxide in the poly (vinyl alcohol) matrix via microwave irradiation. Issue 1 (6th November 2017) - Zhang, Jianwei; He, Yonglyu; Zhu, Pu; Lin, Shaofeng; Ju, Su; Jiang, Dazhi
Abstract : Despite great recent progress, the processing of graphene oxide (GO) sheets in polymers are often one of the most challenging steps in fabricating graphene/polymer nanocomposites. The challenge is how to achieve high levels of dispersion and reduction of GO simultaneously, without any residual reducing agents in the composites. In this work, microwave irradiation is applied as a remote source to in situ reduce GO sheets embedded in the poly (vinyl alcohol) (PVA) matrix, which process maximizes the advantage of GO's solvent processability. The active response of GO to microwave irradiation allows for the uniform and selective heating of GO, leading to a minutes‐quick reduction of GO without physical damage to the polymer matrix. Significant improvements in the mechanical properties, electrical conductivities and glass transition temperatures ( T g s) of GO/PVA nanocomposites are achieved, and possible reasons for the improvements are also discussed. POLYM. COMPOS., 40:170–178, 2019. © 2017 Society of Plastics Engineers